Avaliação termo-hidráulica experimental de grades espaçadoras comerciais para reatores PWR e de protótipo fabricado por impressora 3D - Higor Fabiano Pereira de Castro (2020)
Spacer grids are important components in nuclear fuel assemblies of Pressurized Water Reactors – PWR. These grids are responsible for maintaining the structural integrity of the fuel assemblies and contribute to enhance the thermo-hydraulic efficiency of the reactor. In order to develop a high-efficiency national spacer grid, studies with commercial spacer grids and prototypes manufactured using a 3D printer have been carried out at the Thermo-Hydraulic and Neutronic Laboratory (LTHN) of the Nuclear Technology Development Center - CDTN. Thermo-hydraulic performance of three spacer grids was evaluated in this work: Two types of commercial (mixing vanes and channels) and one printed grid (channels). Spacer grids were tested in different representative nuclear fuel assemblies with a 5x5 square rod bundle. Turbulence parameters were determined from velocities measured downstream of the spacer grids using the Laser Doppler Velocimetry – LDV. For the mixing vanes spacer grid, five flow conditions were evaluated by Reynolds in range of 18x10³ to 54x10³. The comparison tests between these three spacer grids were made for Re = 27x10³. Results showed significant differences in flow behavior for the Re range selected. The comparison results between spacer grids showed that the mixing vane spacer grid is superior to subchannel type and printed grid based on the thermo-hydraulic performance. From the results obtained from the printed spacer grid it was possible to demonstrate the viability of 3D printed prototypes for assessment and development of nuclear fuel assemblies. An experimental benchmark data base was generated for a printed spacer grid and the obtained data can be used as input data in numerical simulation codes and sub-channel thermo-hydraulic analysis and can also be used to validate computational fluid dynamics (CFD) simulations.